Defence is a civil matter first and foremost - Diamint, Rut (2010)
The obsession with security that marked the Bush administration led to at least two counterproductive side effects in Latin America. First, it alienated several Latin American leaders from the US-led agenda, and gave them the fuel to build their own agenda distinct from Washington's single-minded focus. Second, it led to an increase in defence expenditures throughout the region. Many have argued that the United States "lost" Latin America during the Bush administration. The era of the United States as the dominant influence in Latin America is over. What are the new context for Latin American countries?